Risk Factors for Failure in Hammertoe Surgery. (May 2020) - Albright, Rachel H.; Hassan, Moiz; Randich, Jacob; O'Keefe, Robert; Klein, Erin E.; Weil, Lowell; Weil, Lowell; Fleischer, Adam E.
Background: Hammertoe correction is perhaps the most common elective surgery performed in the foot, yet rates of symptomatic recurrence and revision surgery can be high. In this study, we aimed to identify patient and provider risk factors associated with failure after hammertoe surgery. Methods: Consecutive patients with a minimum of 6 months' follow-up undergoing hammertoe surgery within a single, urban foot and ankle practice between January 1, 2011, and December 31, 2013, served as the basis of this retrospective cohort study. Cox regression analysis was used to identify important predictor variables obtained through chart and radiographic review. One hundred fifty-two patients (311 toes) with a mean age of 60.8 ± 11.2 years and mean follow-up of 29.5 ± 21.2 months were included. Results: Statistically significant predictors of failure were having a larger preoperative transverse plane deviation of the digit (hazard ratio [HR], 1.03 for each degree; P < .001; 95% CI, 1.02, 1.04), operating on the second toe (vs third or fourth) (HR, 2.23; P = .003; 95% CI, 1.31, 3.81), use of a phalangeal osteotomy to reduce the proximal interphalangeal (PIP) joint (HR, 2.77; P = .005; 95% CI, 1.36, 5.64), and using less common/conventional operative techniques to reduce the PIP joint (HR, 2.62; P = .03; 95% CI, 1.09, 6.26). Concomitant performance of first ray surgery reduced hammertoe recurrence by 50% (HR, 0.51; P = .01; 95% CI, 0.30, 0.87). Conclusion: We identified risk factors that may provide guidance for surgeons during preoperative hammertoe surgery consultations. This information may better equip patients with appropriate postoperative expectations when contemplating surgery. Level of Evidence: Level III, retrospective case series.